NETRALITAS PEMBERITAAN KAMPANYE TERBUKA OLEH MEDIA MILIK POLITIKUS DAN NON-POLITIKUS - , LUQMAN ZAQIY JATIBENANG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Online news portal, fulfilling its duty as the source of news for public, must be neutral when covering political events. Especially, when approaching the election. Its because the public need neutral informations as guidance for the election. On the other hand, the news media itself later would be the competition arena for the competing parties. The purpose of this study was to compare the neutrality of open (political) campaign news coverage by the medias that were owned by politicians and non-politicians. For this study, the chosen objects were Viva.co.id and Okezone.com as representatives of medias owned by politicians, and Tempo.co and Kompas.com as representatives of medias owned by non-politicians. Open campaign news covered by politiciansâ medias were dominated by unneutral news (Viva.co.id were 62,4% unneutral and Okezone.com were 74,4% unneutral), whereas the non-politiciansâ medias were dominated by neutral news (Tempo.co were 72% neutral and Kompas.com were 68,5% neutral). Furthermore, these were also indicated by the mean score of neutrality, where Viva.co.id got 4,4, Okezone.com got 4,9, Tempo.co got 1,6, and Okezone.com got 2 (with 1 as maximum score for neutrality). Medias owned by politicians tended to favor the ownerâs political party by using unneutral news. This indicated by the major percentage of unneutral-positive news of Golkarâs open campaign covered by Viva.co.id, and Hanuraâs open campaign covered by Okezone.com (each of them 36,4% and 50,6% over total coverage). The same tendency showed by non-politiciansâ medias, but far outnumbered. It can be seen by the minor percentage of unneutral-positive news coverage toward dominant party, PDIP (Tempo.co were 4%, and Kompas.com were 11,3% over total coverage).